PENATAAN KELEMBAGAAN PEMERINTAH DESA BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Rauf, Rahyunir (UIR PRESS, 2016)
The issuance of Law No. 6 of 2014 About Village, for the third time village governed by a separate law, after the first time regulated by Law No. 19 of 1965 On Rural Township and second regulated by Law No. 5 of 1979 About the Village Government. This condition shows the village of serious attention of society, so that people feel the need to make updates. Because during this time the village setting incorporated into the Regional Government Law is considered still many weaknesses in governing the country and have not been able to accelerate the development of the village. Explanation of Law No. 6 of 2014, stated;